Etiological classification and management of dizziness in children: A systematic review and meta-analysis - Zhang, Jifang; Zhu, Qi; Shen, Jiali; Chen, Jianyong; Jin, Yulian; Zhang, Qing; Duan, Maoli; Yang, Jun (Frontiers in Neurology, 2023)
Background Dizziness in children, which could not be diagnosed at an early stage in the past, is becoming increasingly clear to a large extent. However, the recognition of the diagnosis and management remains discrepant and controversial due to their complicated and varied etiology. Central and peripheral vestibular disorders, psychogenic and systemic diseases, and genetic pathogeny constitute childhood etiological entities. Further understanding of the etiology and the prevalence of vertigo disorders is of crucial importance and benefit in the diagnosis and management of pediatric patients. Methods This systematic review and meta-analysis were conducted by systematically searching Embase, PubMed, the Cochrane Library, CNIK, the Chinese Wan-Fang database, CBM, the Chinese VIP database, and the Web of Science for literature on childhood vertigo disorders published up to May 2022. The literature was evaluated under strict screening and diagnostic criteria. Their quality was assessed using the Agency for Healthcare and Research Quality (AHRQ) standards. The test for homogeneity was conducted to determine the fixed effects model or random-effect model employed. Results Twenty-three retrospective cross-sectional studies involving 7,647 children with vertigo disorders were finally included, with an AHRQ score >4 (high or moderate quality). Our results demonstrated that peripheral vertigo (52.20%, 95% CI: 42.9–61.4%) was more common in children than central vertigo (28.7%, 95% CI: 20.8–37.4%), psychogenic vertigo (7.0%, 95% CI: 4.8–10.0%), and other systemic vertigo (4.7%, 95% CI: 2.6–8.2%). The five most common etiological diagnoses associated with peripheral vertigo included benign paroxysmal vertigo of childhood (BPVC) (19.50%, 95% CI: 13.5–28.3%), sinusitis-related diseases (10.7%, 95% CI: −11.2–32.6%), vestibular or semicircular canal dysfunction (9.20%, 95% CI: 5.7–15.0%), benign paroxysmal positional vertigo (BPPV)(7.20%, 95% CI: 3.9–11.5%), and orthostatic dysregulation (6.8%, 95% CI: 3.4–13.0%). Vestibular migraine (20.3%, 95% CI: 15.4–25.2%) was the most seen etiological diagnosis associated with central vertigo in children. In addition, we found the sex-based difference influenced the outcome of psychogenic vertigo and vestibular migraine, while there was no significant difference in other categories of the etiology. For the management of vertigo, symptomatical management is the first choice for most types of vertigo disorder in pediatrics. Conclusion Complex etiology and non-specific clinical manifestations of vertigo in pediatrics are challenging for their diagnoses. Reliable diagnosis and effective management depend on the close cooperation of multiple disciplines, combined with comprehensive consideration of the alternative characteristics of vertigo in children with growth and development.